PEMEROLEHAN NOMINA BAHASA INDONESIA ANAK USIA 3;5 TAHUN: STUDI KASUS SEORANG ANAK DI LUBUK MINTURUN PADANG - Rahayu, Elvina; Agustina, Agustina; Juita, Novia (Universitas Negeri Padang, 2017)
This research aims to (1) describes the form of Indonesian nouns obtained by 3;5 years old children in Lubuk Minturun Padang, (2) describes the type of Indonesian nouns obtained by children aged 3;5 years in Lubuk Minturun Padang. This type of research is qualitative research is using descriptive method. The data of this research is word noun Indonesian used by 3;5 years old children in Lubuk Minturun Padang. Based on the research findings found 2 forms of nouns and 5 types of nouns. The form of the noun, the basic form and the derived form. The types of nouns found are, animate nouns, lifelass nouns, fee nouns, not fairly nouns, and collective nouns.Â Keyword: Indonesian noun, children language